2018
DOI: 10.1038/s41588-018-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Promoter capture Hi-C-based identification of recurrent noncoding mutations in colorectal cancer

Abstract: Efforts are being directed to systematically analyze the non-coding regions of the genome for cancer-driving mutations. cis-regulatory elements (CREs) represent a highly enriched subset of the non-coding regions of the genome in which to search for such mutations. Here we use high-throughput chromosome conformation capture techniques (Hi-C) for 19,023 promoter fragments to catalog the regulatory landscape of colorectal cancer in cell lines, mapping CREs and integrating these with whole-genome sequence and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…Within the last decade, it has become increasingly clear the existence of long-range looping interactions between regulatory elements and promoters, in which onlỹ 7% of all looping interactions are with the nearest gene [80]. These interactions do not only physically exist, but play essential molecular roles in regulating distant gene expression in both biological and pathological settings [47,81]. Long-range integration of DNA methylation and gene expression has already been explored in other disease contexts, in which one study involving a large cohort of colon cancer patients showed that methylation of distal CpGs controlled genes at a distance of > 1 Mb [82].…”
Section: Discussionmentioning
confidence: 99%
“…Within the last decade, it has become increasingly clear the existence of long-range looping interactions between regulatory elements and promoters, in which onlỹ 7% of all looping interactions are with the nearest gene [80]. These interactions do not only physically exist, but play essential molecular roles in regulating distant gene expression in both biological and pathological settings [47,81]. Long-range integration of DNA methylation and gene expression has already been explored in other disease contexts, in which one study involving a large cohort of colon cancer patients showed that methylation of distal CpGs controlled genes at a distance of > 1 Mb [82].…”
Section: Discussionmentioning
confidence: 99%
“…Within the last decade, it has become increasingly clear the existence of long-range looping interactions between regulatory elements and promoters, in which only ~7 % of all looping interactions are with the nearest gene 60 . These interactions do not only physically exist, but play essential molecular roles in regulating distant gene expression in both biological and pathological settings 47,61 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, genes that recurrently exhibit differential ASE may be subject to distal cis regulatory events; the use of known enhancers or Hi-C contact maps may be helpful in constraining the sets of mutations that need to be considered. 62 Alternatively, it is known that there are epigenetic factors that can lead to ASE. 34 Furthermore, even if we find that a gene is dysregulated and suggest observed cis mutations as potentially causative, there may be multiple detected cis mutations and additional analysis is necessary to detect which of those are causing the change in ASE.…”
Section: Discussionmentioning
confidence: 99%